FENOMENA BIAS GENDER PADA KOMUNITAS KPOPERS LAKI-LAKI: STUDI KASUS PADA MAHASISWA KPOPERS FISIP USU MEDAN - Batubara, Nurshafa Ramadhani; Daulay, Harmona; Simanihuruk, Muba; Saladin, T. Ilham (Kafa`ah: Journal of Gender Studies, 2023)
This research is entitled The Phenomenon of Gender Bias in the Male Kpopers Community (Case Study on USU MEDAN FISIP Kpopers Students). This study explains the gender bias that K-Pop fanboys get which is caused by the “collision” of masculinity that society has with that exhibited by K-Pop. This study uses a qualitative research method with a case study approach with informants who are determined by snowball sampling. There were 12 informants in this study with 10 main informants and 2 additional informants. The results of the study show that K-Pop fanboys get gender bias in the form of stereotypes. K-Pop fanboys get gender bias by being labeled as effeminate, feminine, less male, feminine, less masculine, less macho, and gay. The construction of gender bias occurs as a result of the display of soft masculinity by K-Pop idols, the K-Pop market which is dominated by women, the collision of masculinity displayed by K-Pop with masculinity presents in societu (macho), inferiority of femininity, incongruity with gender views openness to femininity, not trapped in the construction of masculinity and the application of soft masculinity by K-Pop fanboys in everyday life simply in the sense that it is not too soft masculinity.